1994
DOI: 10.1007/bf00926033
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the inhibitory effects of curcumin and eugenol on the formation of reactive oxygen species and the oxidation of ferrous iron

Abstract: The spice principles curcumin (from turmeric) and eugenol (from cloves) are good inhibitors of lipid peroxidation. Lipid peroxidation is known to be initiated by reactive oxygen species. The effect of curcumin and eugenol on the generation of reactive oxygen species in model systems were investigated. Both curcumin and eugenol inhibited superoxide anion generation in xanthine-xanthine oxidase system to an extent of 40% and 50% at concentrations of 75 microM and 250 microM respectively. Curcumin and eugenol als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
1
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(149 citation statements)
references
References 35 publications
6
139
1
3
Order By: Relevance
“…), 2,2 0 -azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS .+ ) and N,N-dimethyl-p-phenylenediamine dihydrochloride (DMPD .+ ) radical (Reddy & Lokesh 1994;Fujisawa et al 2004;Ak & Gulcin 2008;Trujillo et al 2013). The antioxidant capacity of curcumin is also related to the inhibition of lipid peroxidation and the induction of nuclear factor E2-related factor 2 (Nrf2) translocation to the nucleus.…”
Section: Curcuminmentioning
confidence: 99%
“…), 2,2 0 -azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS .+ ) and N,N-dimethyl-p-phenylenediamine dihydrochloride (DMPD .+ ) radical (Reddy & Lokesh 1994;Fujisawa et al 2004;Ak & Gulcin 2008;Trujillo et al 2013). The antioxidant capacity of curcumin is also related to the inhibition of lipid peroxidation and the induction of nuclear factor E2-related factor 2 (Nrf2) translocation to the nucleus.…”
Section: Curcuminmentioning
confidence: 99%
“…9 Several studies have demonstrated the antioxidant capacity of the eugenol and related compounds (like isoeugenol) to inhibit the lipidic peroxidation induced by reactive oxygen species. 11,12 It also inhibits the superoxide radical formation in the xanthine-xanthine oxidase system. 13 E1 can inhibit the hydroxyl radical generation, and can prevent the Fe 2+ oxidation in the Fenton reaction that generates the radical.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, MMS has been observed as oxidative-stress inducer (Horvaathovaa et al 1998). Curcumin due to its free radical scavenging property, by acting as electron donor and inhibition of lipid peroxidation acts as an antioxidant (Reddy andLokesh 1994, Sreejayan andRao 1994). Oxidative stress is the cause of many diseases, while curcumin has the ability to cure many diseases like diabetes and cancer due to its antioxidant capacity (Sajithlal et al 1998, Majithi et al 2005, Saha et al 2010.…”
Section: Discussionmentioning
confidence: 99%